Contemporary Art Gallery (Expressionism Architecture) - Fazra Risky Nasution; Morida Siagian (International Journal of Architecture and Urbanism, 2020)
Some issues prove that the development of art in Medan is relatively slow and does not become a concern of the public because of the availability of minimal and inadequate space, while Medan is a multicultural city in terms of art, many artists in the city of Medan have great potential. The construction of contemporary art gallery aims to meet the needs and facilities of art activities in the city of Medan because Medan does not yet have a decent art gallery for art activities, from exhibitions, artwork making space, to fine arts training venues and also as a center for art development likeness of the City of Medan. This gallery plans to be a productive place or place to introduce and provide attractive insights or knowledge to local people and tourists and to be able to preserve and preserve the fine arts in the city of Medan. The methodology used in this project is by collecting data through from literature review and by doing a site surveys. This building design uses the theme of expressionism architecture, where this building can express the meaning of art that it can be enjoyed visually.